2014
DOI: 10.1021/jp409807x
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor Concentration Dependence of Förster Resonance Energy Transfer Dynamics in Dye–Quantum Dot Complexes

Abstract: The dynamics of the photoinduced Forster resonance energy transfer (FRET) in a perylene diimide−quantum dot organic−inorganic hybrid system has been investigated by femtosecond time-resolved absorption spectroscopy. The bidentate binding of the dye acceptor molecules to the surface of CdSe/CdS/ZnS multishell quantum dots provides a well-defined dye-QD geometry for which the efficiency of the energy transfer reaction can be easily tuned by the acceptor concentration. In the experiments, the spectral characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 69 publications
5
64
0
2
Order By: Relevance
“…85,95,96 A study performing ligand exchange between native oleic acid ligands and carboxylate acid functionalized boron-dipyrromethene dye found that NCs have multiple, identical binding sites. 85,95,96 A study performing ligand exchange between native oleic acid ligands and carboxylate acid functionalized boron-dipyrromethene dye found that NCs have multiple, identical binding sites.…”
Section: Quantification and Study Of Ligand Binding Sitesmentioning
confidence: 99%
“…85,95,96 A study performing ligand exchange between native oleic acid ligands and carboxylate acid functionalized boron-dipyrromethene dye found that NCs have multiple, identical binding sites. 85,95,96 A study performing ligand exchange between native oleic acid ligands and carboxylate acid functionalized boron-dipyrromethene dye found that NCs have multiple, identical binding sites.…”
Section: Quantification and Study Of Ligand Binding Sitesmentioning
confidence: 99%
“…32,43,47 It has also been indicated that, for NC−dye conjugates with R DA > R 0 , eq 4 provides an accurate estimate of the donor−acceptor distances. 47 If the number of bound acceptor species is small compared to the number of possible binding sites (such as 1 acceptor per 20 binding sites), then the distribution of the acceptors per donor NC will obey the Poisson statistics and a modified equation for η may be more appropriate: 48 Here, ξ is the mean number of acceptor molecules bound to each donor NC, and n is the whole actual number of the acceptor molecules. Similarly, R DA for a system with a fixed donor/acceptor ratio can then be calculated using η and R 0 , assuming a constant acceptor distribution per donor NC: 32,43,47 …”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since the number of quenching molecules bonded to a QD obeys a Poisson distribution [8], an exponential function fitted well the dependence of the relative QD PL intensity on the relative acceptor concentration in the mixture ("quenching curve") [9]. In this case, the relative PL intensity of the QDs can be expressed by the equation:…”
Section: Complexes Of Quantum Dots and Chlorin E6 Formed Due To Electmentioning
confidence: 87%